Model Of Information Disclosure In A Multilevel Social-Economic System With Information Asymmetry By The Example Of A Regional Market Of Property Rights - Alim Gurtuev, Muslim Chazhaev, Rustam Yalmaev, Zaur Ivanov, Aminat Dumanova, Macca Yalmaeva (International Journal of Advanced Science and Technology, 2020)
The behavior of economic agents in an innovative process may be reduced to the problem of decision making under uncertainty in Knight’s sense. The primary problem is that of cognitive limitations, characteristic for actual economic agents. It allows opportunism, i.e. inclination of individuals to deceive or to distort information for their own advantage, doing that in an indirect way. Bounded cognitive abilities and opportunism, taken together, result in the problem of knowledge asymmetry – namely, even if the information about essential aspects of a deal is available to all its participants, one of the parties lacks competences necessary to process that information.